New Distributional Records and Checklist of Lichens for Andhra Pradesh, India - Madhusudhana Reddy, A.; Nayaka, Sanjeeva; Chandramati Shankar, P.; Rajagopal Reddy, S.; Ravi Prasad Rao, B. (Indian Forester, 2011)
The present communication reports 12 new lichen species for the first time from the state of Andhra Pradesh. Many of them were foliose lichens while Chrysothrix chlorina, Diorygma junghuhnii and Hafellia curatellae are the only crustose forms. A brief description of the species and their distribution in India are provided for all the taxa. The checklist of 43 lichens so far reported from Andhra Pradesh is also provided. The study clearly indicates the enormous scope for lichenological investigations in the state and could act as baseline for future biomonitoring, bioprospection and biodiversity studies.